ANALISIS PENGARUH KETIDAKPUASAN KONSUMEN, HARGA DAN KEBUTUHAN MENCARI VARIASI TERHADAP PERPINDAHAN MEREK SABUN LIFEBUOY DI SEMARANG - Ratna Nilasari, Debora; Yoestini, Yoestini (Faculty of Economics and Business Diponegoro University, 2012)
This study aims to determine the effect of consumer dissatisfaction, price and the need to variety product of brand switching decision of bar soap. This research was conducted on consumers Lifebuoy bar soap that has been moved to another brand of soap and bar soap sample set of 100 respondents using Accidential Sampling methods. Data ware collected by distributing questionnaires. Data analysis method was perfored by multiple linear regression using SPSS software. Data that has met the test validity, test reliability, and test the assumptions of classical. Based on analysis that used, can be pulled several conclusions of be donedoubled regression processing. this watchfulness is validity up to standard,reliabilitas, with free from heteroskedastisitas, multikolinearitas and escape testnormally. from regression similarity that got, variable dependent that has value most significant that is consumer dissatisfaction. hypothesis testing by using test t demo that variable consumer dissatisfaction, price and the need for variety, variables according to significant influence displacement brand. while in test f demo significant <0,05. matter thismeans variable displacement Brand (Y), Consumer Dissatisfaction (X1), Price (X2) and Needs Finding Variations (X3) to together influential manifestly towards displacement brand (Y). while determination coefficient is got with value adjusted R Square 48,4%, mean, variable displacement brand explainable by existence variable consumer dissatisfaction, price, advertising and the need for variety, while therest 51,6% can be influenced by variable other.